The role of institutional quality on the effects of fiscal stimulus - Leopoldo Avellán; Arturo José Galindo Andrade; John León-Díaz (Inter-American Development Bank (IDB), 2020)
This paper provides evidence on the effect of fiscal stimulus on economic activity in countries with different degrees of institutional quality. The identification strategy makes use of data on military expenditure to instrument government consumption using local lineal projections as presented in Jordà (2005 ). Based on a panel of 113 countries during the period 1988-2017 , the analysis finds evidence that an increment of 1 percent in government consumption yields a sizable, persistent, and stable increase in economic activity of 0.9 percent in countries with higher institutional quality. In contrast, for countries with lower institutional quality, the effect is smaller (0.4 percent) and more short-lived
Keywords: E02; E32; E62; 330; fiscal policy; economic activity; institutional quality